Why African road deaths do not matter. (1st March 2011) - Kobusingye, O
Abstract : Africa has one of the highest road fatality rates worldwide. It also appears to be doing the least about it. Over the last few decades while road deaths in High Income Countries (HICs) dropped, numbers in African countries, and elsewhere in Low and Middle Income Countries (LMICs), rose. Many factors resulted in the success in the HICs: implementation of interventions that spanned land use and safer road infrastructure, safer vehicles, strict enforcement of speed, drink-driving, and occupant restraints, and improved post-crash care. Underlying all this was focused and sustained research, and continued improvement of road safety data. And perhaps most important, the cost of road crashes and deaths has become unacceptable to society in HICs. Riding on the success in HICs, the road safety community has been determined to improve data, particularly in LICs where gross under-reporting, even of deaths, is commonplace. In 2007 the World Health Organisation's African Region reported 52 302 deaths on the region's roads – a rate of 7.2 deaths per 100 000 population. This would have ranked African roads as the safest in the world, ahead of the European region's 12.8 deaths per 100 000 population. When the figures were modelled to address incomplete reporting, and to harmonise the definitions for a road fatality, it was estimated that 234 768 persons died on African roads, a rate of 32.2 deaths per 100 000 population. A major concern among the road safety community has been that few costing studies are available in regions where rates for road deaths and injuries are highest. But there is no indication that in fact cost will have the same impact on policy that it has had in HICs. It might be that the cost of African lives does little to impress African policy makers.